Ответы 2

  • Спасибо
  • 16^(cos^2x)+16^(1-cos^2x)=1016^(cos^2x)+16/16^(cos^2x)-10=0Заменим 16^(cos^2x)=tt+16/t-10=0  (*t)t^2-10*t+16=0t1,2=(10±√(100-64))/2=(10±6)/2t1=2   16^(cos^2x)=2  2^(4*cos^2x)=2^1    4*cos^2x=1  cos^2x=1/4   cosx=±1/2    x=±П/3+Пn, nЄZt2=8   16^(cos^2x)=8    2^(4*cos^2x)=2^3   4*cos^2x=3  cos^2x=3/4cosx=±√3/2   x=±П/6+Пm, mЄZ[-П/2; П]  х=-П/3; -П/6; П/6; П/3; 2*П/3; 5*П/6
    • Автор:

      tater
    • 4 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years